CORPORATE CRIMINAL LIABILITY IN ILLEGAL LOGGING DUE TO EXPLOITATION OF NATURAL RESOURCES - Agustin H, Nurfarida Nuya (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
The practice of illegal logging represents a significant challenge to the sustainability of Indonesia's forests. This is because the negative impact of this practice extends beyond the loss of biodiversity to encompass climate change and the welfare of local communities. The main objective of this research is to determine the criminal liability of corporations involved in illegal logging due to the exploitation of natural resources. The method used in this research is normative analysis, which includes an approach to legislation and a case approach. The findings indicate that despite strict regulations, the effectiveness of criminal law in preventing illegal logging is constrained by several operational challenges. These challenges include corruption, inadequate resources, and lack of public awareness. Therefore, corporate criminal liability must be strictly enforced to effectively address the detrimental impacts of illegal logging practices on the environment and local communities while ensuring the sustainability of natural resources for future generations. The findings of this study indicate the need for increased collaboration, stronger law enforcement measures, and greater community engagement. They can contribute to developing more effective forest protection policies and preventing illegal logging in Indonesia.